Family Health Strategy: characterization of users diagnosed with Mental Health (Research, Society and Development, 2021)
Objective: to characterize users with mental health diagnosis who access a Family Health Strategy in a city in the state of Rio Grande do Sul. Methodology: cross-sectional and descriptive study. After data collection, descriptive statistical analysis is performed. Results: the sample consisted of 266 medical records. The average age of users was 59.07 years, with 80.5% being female. Depression was the most prevalent diagnosis, followed by anxiety disorder. Single users predominate (13.2%), 40.6% live with family and / or partner, 38.7% had incomplete primary education, 77.1% used antiepressants and 50.4% benzodiazepines, 15.4 % use two different antidepressants, 1.5% two anticonvulsants and 2.3% two antipsychotics. Conclusion: the lack of information in the medical records was identified, limited the characterization of users. Depression was the most prevalent diagnosis, a situation that reinforces it as an important public health problem.